Rahasia Saintifik dibalik Ibadah Sunnah Berenang - Ermin, Anastasya; Fakhruddin, Agus (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
Health is important for every human being. Likewise, Islam advocates for a healthy life and being a strong human both spiritually and physically, and motivates its people to do physical activities that are useful for boy health. Islam shows the virtue of strength and health as a major asset in pious deeds and activites in religious affairs and world affairs of a Muslim. Swimming is one of the sports that recommended by Prophet Muhammad, based on the hadith narrated by Imam Bukhari. Swimming is a sport that is done in water, involving almost all muscles in the body to move. Swimming is a fun and not boring sport. This study uses a qualitative descriptive approach to the type of library research. The benefits of swimming for the health, based on the results of this study are it can increase cardiovascular strength, burn 24% of body calories, can overcome joint pain, osteoporosis, and asthma, can increase the production of endorphins so as to reduce emotional feelings, both for pregnant and elderly, and improve children’s brain development.